Presence data for the seven most widespread European shrews and R code for two Joint Species Distribution Models - Neves, Tomé (PANGAEA, 2023)
This dataset includes European presence data and sources for Crocidura leucodon, Crocidura suaveolens, Crocidura russula, Sorex araneus, Sorex coronatus, Sorex minutus and Suncus etruscus. Gathered from GBIF and several European museums. Further, it includes the code to run two distinct Joint Species Distribution Models (JSDM): Pollock et al. (2014) and Clark et al. (2018).
Keywords: Europe; Shrews; Soricidae